EFFICACY, IMMUNOGENICITY AND SIDE EFFECT OF COVID-19 VACCINE ON PREGNANT AND LACTATING WOMEN: A SYSTEMATIC REVIEW - Sukarno, Anita; Kurniawan, Mohammad Heri; Awaluddin, Achmad Indra (Journal of Islamic Nursing, 2021)
Purpose: To investigate the efficacy, immunogenicity, and side effect of the Covid-19 vaccine on pregnant and lactating women. Methods: We obtained 1366 articles from 7 databases such as PubMed, Google Scholar, ScienceDirect, Cochrane Library, EU Clinical Trials Register, ClinicalTrials.gov, the WHO Clinical Trial Registry. The search terms were “Covid-19 Vaccine”, “Sars-Cov-2 Vaccine”, “Vaccine Efficacy”, “Vaccine Immunogenicity”, “Vaccine Side Effect“, “Pregnant Women”, and “Lactating Women”. Study selection and study quality appraisal were guided by Joanna Briggs Institute (JBI). Results: Fifteen articles were included. Vaccinated pregnant women had a lower risk of Covid-19 infection. Immune responses were detected in maternal blood, cord blood, and breast milk. The T-cell had the potential to against viral variants. Covid-19 vaccination resulted in low disruption among lactating women. There was no difference in side effects between pregnant and nonpregnant women. Conclusions: Covid-19 vaccine lowered infection risk and robust immune responses among pregnant and lactating women.